THE CONCEPT OF AL-'ILM AL-USHULIY: THE SIGNIFICANCE OF USHUL FIQH IN THE UNITY OF SCIENCE PARADIGM - Majid, ILHAM MAJID; Zukhruf , Ahmad Zukhruf Nafis K (UIN Sunan Kalijaga Yogyakarta, 2024)
Abstract This research aims to explore the significance of Ushul Fiqh within the paradigm of the unity of knowledge (Unity of Science), focusing on the integration between Islamic law and other sciences. The main concern is how Ushul Fiqh can provide a holistic theoretical foundation for religious values such as wisdom, justice, and public welfare in everyday life. This study employs a qualitative method with a descriptive-analytical approach, utilizing a literature review to explore the meaning, perception, and complex context within a research framework. Key findings indicate that Ushul Fiqh plays a crucial role in understanding the fundamentals of Islamic law and integrating religious aspects, reason, and practical experience in life. This research aims to identify and analyze the principles of Ushul Fiqh that can support the integration of various scientific disciplines and assess their relevance in the context of contemporary knowledge. The unity of knowledge in this research refers to efforts to amalgamate various disciplines into an interconnected entity. This involves integrating Islamic law (Ushul Fiqh) with other sciences, such as logic, Arabic grammar, theology, jurisprudence, and Qur'anic and Hadith studies. In this context, the unity of knowledge aims to create coherence among various branches of knowledge to provide a holistic understanding of religious values such as wisdom, justice, and public welfare in everyday life. Keywords: Ushul Fiqh, Significance, Paradigm, Unity of Science